Common currencies and FDI flows - Stefano Schiavo (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2005)
The paper investigates the impact of EMU on foreign direct investment flows. Using the option value approach to investment decisions, it is possible to show how exchange rate uncertainty hinders cross-border investment flows. By permanently fixing bilateral exchange rates, a currency union can then be expected to spur international investment. Results from a gravity model on a sample of OECD countries confirm the hypothesis that currency unions have a positive impact on FDI; moreover, adopting the same currency appears to do more than merely eliminating exchange rate volatility. These findings closely resemble those recently obtained in the trade literature.
Keywords: F15; F21; 330; Eurozone; Auslandsinvestition; Optimaler Währungsraum; Gravitationsmodell; EU-Staaten; OECD-Staaten